Pachyonychia congenita 1/Chronic mucocutaneous candidosis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Pachyonychia congenita 1 (PC1) is an inherited skin disorder due to the mutation of a gene codifying for K6a and K16 keratins. Autosomal dominant chronic mucocutaneous candidosis is due to a primary immune deficiency. Although being very different diseases, the nail involvement in both of them can give rise clinically to diagnosis problems.